THE CONCEPT OF «RISK SOCIETY» WITHIN THE CONCEPTUAL APPARATUS OF PUBLIC ADMINISTRATION - Liliia Muntian (Публічне управління та регіональний розвиток)
The article explores the necessity for a theoretical and conceptual understanding of the concept of «risk society» as a category of public administration in the context of globalization. The processes of globalization exacerbate crises, intensify competition for access to limited and non-renewable resources, and create uncertainty, accelerating the emergence of new types of risks. Consequently, risk has become an integral feature of modern society, leading instability and transforming it into a high-risk society. It is highlighted that risks reduce the level of controllability in the country and at the same time increase the emergence of new risks and the likelihood of errors in government decision-making. In conditions of uncertainty, it is difficult to take into account the maximum number of emerging factors. It is noted that the continued existence and development of humanity depend on the identification and anticipation of risk situations, as well as the implementation of timely measures aimed at preventing them and minimize the negative consequences. It is emphasized that in the context of globalization-related risks, public administration bodies must seek innovative tools and mechanisms to ensure effective management of society. It has been established that in Ukraine, risks manifest in various forms in almost all sectors, they worsen public administration, prevent the authorities from solving economic and social problems in a timely manner. The government’s ineffective response to these risks provokes new risks and undermines public trust. This has drawn the scholar’s attention to interpreting the concept of «risk society» as a category of public administration, emphasizing decision-making processes aimed at risk minimization. This raises the question of understanding the substantive content of risk in relation to decision-making in public administration and recognizing it as a key category of public administration. Further research should focus on studying risks in modern society, particularly, in the context of strengthening the power of transnational companies, which have their own dynamics, whose activities reflect not only negative but also positive aspects.